Ta’rīb Musṭalahati al-Harbi wa al-Siyāsati fī al-Iblāghi ‘An al-Ṣirā’i fī Jazīrati al-‘Arabiyyah - Diva, Shafa; Mahendra, Ahdiyat; Yusuf, M. (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
Language functions as a tool for communication between humans, allowing them to express their thoughts and intentions. Language also evolves due to interactions between neighboring languages, and this is true for Arabic as well. The evolution of Arabic includes the incorporation of new vocabulary through the process of borrowing, which is often referred to as Arabization. Therefore, this study explores Arabization with the aim of identifying the forms of Arabization and the languages from which the borrowed words originate. This research focuses particularly on newspapers, as they play a significant role in introducing new vocabulary through their reporting. News about war and political conflicts frequently captures global attention, especially regarding the conflicts in the Middle East. This study employs a qualitative method with a descriptive analytical approach. The primary data sources are three online newspapers from the Middle East: As-Syarq (Qatar), Al-Ittihad (UAE), and SabaNet (Yemen). The findings indicate that Arabization occurs through several methods, including Iqtibas Al-Lafdzi (literal borrowing), translation, and derivation. A total of 54 instances of Arabization using the Iqtibas Al-Lafdzi method and 6 instances using translation were identified in the war and political reporting of the three newspapers (As-Syarq, Al-Ittihad, and SabaNet) between November 1–10, 2023. The study found nine source languages: Greek, Latin, English, Persian, French, Russian, Japanese, Hebrew, and Syriac.